A New Family of Two‐Dimensional Zeolites Prepared from the Intermediate Layered Precursor IPC‐3P Obtained during the Synthesis of TUN Zeolite. Issue 41 (23rd August 2013) - Kubů, Martin; Roth, Wieslaw J.; Greer, Heather F.; Zhou, Wuzong; Morris, Russell E.; Přech, Jan; Čejka, Jiří
Abstract The crystallization of zeolite TUN with 1, 4‐bis(N‐methylpyrrolidinium)butane as template proceeds through an intermediate, designated IPC‐3P, following the Ostwald rule of successive transformations. This apparently layered transient product has been thoroughly investigated and found to consist of MWW monolayers stacked without alignment in register, that is, disordered compared with MCM‐22P. The structure was confirmed based on X‐ray diffraction and high‐resolution (HR)TEM analysis. The layered zeolite precursor IPC‐3P can be swollen and pillared affording a combined micro‐ and mesoporous material with enhanced Brunauer–Emmett–Teller (BET) surface area (685 m2g−1) and greater accessibility of Brønsted acid sites for bulky molecules. This mesoporous material was probed with 2, 6‐di‐tert‐butylpyridine (DTBP). IPC‐3P and its modification create a new layered zeolite sub‐family belonging to the MWW family. FTIR data indicate that (Al)MWW materials MCM‐22 and IPC‐3 with Si/Al ratios greater than 20 exhibit a lower relative ratio of Brønsted to Lewis acid sites than MCM‐22 (with Si/Al ratios of around 13), that is, less than 2 versus more than 3, respectively. This is maintained even upon pillaring and warrants further exploration of materials like IPC‐3P with a higher Al content. The unique XRD features of IPC‐3P indicating misaligned stacking of layers and distinct from MCM‐22P, are also seen in other MWW materials such as EMM‐10P, hexamethonium‐templated (HM)‐MCM‐22, ITQ‐30, and UZM‐8 suggesting the need for more detailed study of their identity and properties.